THE EFFECT OF SERVICE QUALITY, PRODUCT EXELLENCE AND PROMOTION ON CONSUMER SATISFACTION CV. PRIMAJAYA SARANA - Arief Dermawan (UPMI Management, 2022)
This study intends to determine the partial effect of service quality, product excellence, and promotion on consumer satisfaction at CV. Prima Jaya Sarana. All the population in this study is consumers who are spread in Yogyakarta. The sample taken is 60 respondents who are suitable and matched as data sources. The distribution uses Accidental Sampling. The measurement scale uses a Likert scale. Hypothesis testing uses partial test (t test), simultaneous test (F test), and coefficient of determination test (R2), while data processing uses SPSS version 24. The results of this study indicate that partially the quality of service shows a value of 3.634 which means it has a positive and significant effect on consumer satisfaction; partially, product excellence shows a value of 3.312 which means that it has a positive and significant effect on consumer satisfaction and partially promotion shows a value of 2.765 has a positive and significant effect on consumer satisfaction, simultaneously the variables of service quality, product quality, and promotion have a positive and significant effect to customer satisfaction as indicated by a value of 46,348. The influence of service quality, product quality, and promotion variables on purchasing decisions is 69.8%.